The reality of the job leakage in the General Corporation for Desalination of Saline Water in Jubail Station - Marshad, Almutairi Fheed (Journal of Economic, Administrative and Legal Sciences, 2019)
The study aimed to find out the causes of Job Dropout in the General Corporation for Saline Water Conversion in Jubail. The study used the survey method. The population of the study were (1900)، and the results reached the most important results: The sample highly approved by (74. 6%) and a mean of (3. 73). And that the stability of salary without bonuses is the most important of these reasons and may be attributed to the weakness of the organizational structure in the institution and not to update. The study also revealed that the physical and organizational dimension is considered to be the most important cause of the Job Dropout in the firm، with an average of (4. 73) percentage، 87. 4%. And that the provision of medical insurance was arithmetic repetition of (123) percent by 95. 4 percent، as well as the non-provision of housing allowance was of arithmetic repetition of (114) and 88. 4 percent. The study also showed that after social and personal factors came to a medium degree. The responses to this dimension were averaged (33. 3) and 66. 6%. The responses of (119) individuals، 92. 3%، indicated that they prefer to drop out of the institution when there are offers at another establishment. The study concluded the following recommendations: The need for the organization to know the reasons for the leakage of its employees by making sure to interview with the actual dropouts and to benefit from this information in the reformulation of future policies for human resources. Approval of medical insurance programs for employees of the General Corporation for Desalination of Salt Water in Jubail. Review the organizational and administrative structure. Review and amend the upgrade regulations in force in the institution in proportion to similar establishments. Provision of housing allowance for the employees of the institution for those who do not have housing. Revising and working on the financial incentive program to distribute it fairly.
Keywords: causes of job dropout; material incentives